Composite repair: On the fatigue strength of universal adhesives - Stape Thiago Henrique Scarabello; Tulkki Oskari; Salim Ikram Aqel; Jamal Kaveh Nik; Mutluay Mustafa Murat; Tezvergil-Mutluay Arzu (ELSEVIER SCI LTD, 2022)
Objectives: To determine whether the composition of universal adhesives and the use of silane coupling agents could affect the fatigue strength of composite repair.
Methods: Composite samples were aged in water at 37 degrees C for 90 days and bonded to fresh composite to produce twin-bonded bar-shaped composite specimens (2 x 2 x 12 mm). Five universal adhesives, a multistep composite repair system and a hydrophobic solvent-free resin associated to a separate silane coupling agent application were used for bonding. Composite samples were tested under 4-pointflexure initially at quasi-static loading (n = 12) followed by cyclic loading (n = 25). The stress-life fatigue behavior was evaluated following the staircase method at 4 Hz. The unfractured side of cyclic loaded beams were evaluated under SEM to determine crack initiation sites. Fatigue data was analyzed by ANOVA and Tukey test and Wilcoxon Rank Sum Test (alpha = 0.05).
Results: Bonding protocols were unable to restore the cohesive strength of the nanofilled composite (p < 0.05). Fatigue testing was more discriminative to reveal discrepancies in composite repair than conventional quasi-static loading. While the composition of universal adhesives affected composite repair potential, the highest endurance limits occurred for the separate silane coupling agent application. Crack propagation sites were mostly located on the aged composite surface.
Significance: Although a trend for simplification invariably overruns current adhesive dentistry, composite repair using solely universal adhesives may result in inferior repair potential. The additonal use of silane coupling agents remains as an important procedure in composite repairs.
(c) 2021 The Author(s). Published by Elsevier Inc. on behalf of The Academy of Dental Materials. CC_BY_NC_ND_4.0